Implementasi Kebijakan Sekolah Gratis Di Indonesia: Studi Pada Sekolah Menengah Kejuruan Negeri (SMKN) Kabupaten Kutai Kartanegara - Rahman, Edi; Salam, Rahmat; Mukhlishin, Mukhlishin (Universitas Muhammadiyah Mataram, 2024)
This research is based on the implementation of the free school policy in State Vocational High Schools (SMK) in Kutai Kartanegara Regency. Although this policy aims to improve access to education and ease the economic burden of low-income families, its implementation faces a number of significant obstacles. The main objective of this study is to analyze the free school policy implementation process deeply, focussing on the evaluation of free school policy implementation in Kutai Kartanegara, the impact on education quality, student motivation and achievement, and stakeholders' perceptions. This study used qualitative methods with a population consisting of SMKN in Kutai Kartanegara Regency, and samples were taken from two SMKN in the middle, upstream, and downstream sections. Descriptive and content analysis methods analyzed data from interviews and observations. The results show that: 1) The policy has been successful in some aspects, such as improving access to education, but there are serious obstacles that hinder the achievement of optimal results. These include inadequate facilities, limited resources, and ineffective fund management. The findings enrich the existing literature by showing that greater attention to technical and managerial aspects is needed to achieve the long-term success of the free school policy. 2) There is a decrease in learning motivation among some students from well-off families, which seems to be due to the perception that education becomes less valuable when no fees are charged. This highlights the need for adjustments in the policy to ensure that the free school program provides balanced benefits to all students, regardless of their economic background.